When and How Do Interactive Digital Media Help Children Connect What They See On and Off the Screen?. (22nd May 2018) - Kirkorian, Heather L.
Abstract: Understanding screen media—even television—can be a challenging task that requires substantial cognitive effort, especially for young children with relatively limited cognitive resources. Toddlers are less likely to transfer information across contexts (e.g., from video images to actual objects) than within the same context. Interactivity, such as that afforded by video chat and touchscreen mobile applications, may promote this transfer. However, some types of interactivity may be more beneficial than others, and the optimal conditions for learning differ across children. In this article, I describe what we know and what we need to understand more fully about children's transfer in the context of interactive digital media. I emphasize the extent to which cognitive constraints and the complexity of tasks likely moderate the effects of digital media on early learning and development.